Possibility of replacing conventional organic solvents with green Deep Eutectic Solvents in drug analysis - Vasilić, Djordje; Rašević, Marija; Zečević, Mira; Čarapić, Marija; Malenović, Andjelija (Archives of Pharmacy, 2024)
In recent years, Deep Eutectic Solvents (DESs) have attracted increasing attention in various scientific disciplines. Their unique properties, such as low toxicity, biodegradability, low cost and versatility, have made them an attractive alternative to conventional organic solvents. In pharmaceutical analysis, where the demand for environmentally friendly methods is growing, questions regarding whether DESs can replace organic solvents as "green solvents" have arisen. This paper explores the potential applications of DESs in drug analysis, and highlights the benefits and challenges they bring. Examples of the use of DESs in chromatographic techniques and in the extraction of drugs from various samples are presented. Additionally, research on the stability and toxicity of DESs in analytical applications is discussed. Based on the available data, it could be concluded that DESs have the potential to become an important component of analytical methods in pharmaceutical analysis and provide environmentally sustainable and efficient alternatives to conventional organic solvents. However, further research is needed to better understand their properties and optimize their application in drug analysis.